Antigen‐specific CD4+CD25+ T cells induced by locally expressed ICOS‐Ig: the role of Foxp3, Perforin, Granzyme B and IL‐10 ‐ an experimental study. (16th July 2019) - Christiansen, Dale; Mouhtouris, Effie; Hodgson, Russell; Sutton, Vivien R.; Trapani, Joseph A.; Ierino, Francesco L.; Sandrin, Mauro S.
Summary: We have previously reported that ICOS‐Ig expressed locally by a PIEC xenograft induces a perigraft cellular accumulation of CD4 + CD25 + Foxp3 + T cells and specific xenograft prolongation. In the present study we isolated and purified CD4 + CD25 + T cells from ICOS‐Ig secreting PIEC grafts to examine their phenotype and mechanism of xenograft survival using knockout and mutant mice. CD4 + CD25 + T cells isolated from xenografts secreting ICOS‐Ig were analysed by flow cytometry and gene expression by real‐time PCR. Regulatory function was examined by suppression of xenogeneic or allogeneic primed CD4 T cells in vivo . Graft prolongation was shown to be dependent on a pre‐existing Foxp3 + Treg, IL‐10, perforin and granzyme B. CD4 + CD25 + Foxp3 + T cells isolated from xenografts secreting ICOS‐Ig demonstrated a phenotype consistent with nTreg but with a higher expression of CD275 (ICOSL), expression of CD278 (ICOS) and MHC II and loss of CD73. Moreover, these cells were functional and specifically suppressed xenogeinic but not allogeneic primed T cells in vivo .